A Straightforward Conversion of Activated Amides and Haloalkanes into Esters under Transition-Metal-Free Cs2CO3/DMAP Conditions - Jian, Junsheng; Wang, Zijia; Chen, Liuqing; Gu, Ying; Miao, Liqiong; Liu, Yueping; Zeng, Zhuo (Synthesis, 2019)
The esterification of activated amides, N-acylsaccharins, under transition-metal-free conditions with good functional group tolerance has been developed, resulting in C–N cleavage leading to efficient synthesis of a variety of esters in moderate to good yields. This work demonstrates that esterification may proceed by using simple N-acylsaccharins, haloalkanes, and Cs2CO3 as oxygen source.
Keywords: esterification; amides; metal-free; haloalkanes; C–N cleavage